The investigation of the stabilization of the structure of aqueous solutions of hexamethylphosphortriamide using an acoustic method - MIECZNIK, Piotr (Archives of Acoustics, 1980)
Measurements of the density and of ultrasonic velocity at a frequency of 15 MHz in aqueous solutions of hexamethylphosphortriamide (IIMPT) over the temperature range 283.15–423.15 K for the whole concentration range are reported. On the basis of the quantities measured, the adiabatic compressibility, the deviation of the molar volume of the solution from the additive volume, the partial molar volumes and partial molar compressibilities of the components have been calculated.The sharp extremes of the ultrasonic velocity, the adiabatic compressibility, the excess compressibility and the partial molar volumes occurring in the range of low concentrations of HMPT (0.04(323.15 K)–0.07(283.15 K) molar fraction) can be attributed to the stabilization of the structure of water in the solution in consequence of the growth of clathrate structures of composition 8X ·136 H2O. The variations of the dependence of the partial molar compressibilities of the components on the concentration indicate a strong intramolecular interaction between the components in a solution, and in particular, over the range of low HMPT concentrations.